Patterns of Dyadic Appraisal of Decision-Making Involvement of African American Persons Living With Dementia. (1st July 2020) - Bonds, Kalisha; Song, MinKyoung; Whitlatch, Carol J; Lyons, Karen S; Kaye, Jeffrey A; Lee, Christopher S
Abstract: Background and Objectives: Greater everyday decision-making involvement by persons living with dementia (PLWD) and congruent appraisal between PLWDs and their caregivers have been associated with a better quality of life (QOL) for both members of the dyad. However, no study has examined the association between the appraisals of everyday decision-making involvement of PLWDs and their QOL among African Americans. Research Design and Methods: A secondary analysis of cross-sectional data from 62 African American dementia dyads was conducted. Multilevel and latent class mixture modeling was used to characterize dyadic appraisal of the decision-making involvement of African American PLWDs and identify distinct patterns thereof. Results: Three distinct patterns were observed. "Incongruent, PLWD Low Involvement" labeled 19.4% of the sample, 53.2% were labeled "Incongruent, PLWD Moderate Involvement, " and 27.4% were labeled "Congruent, PLWD High Involvement." The Congruent, PLWD High Involvement pattern consisted of PLWDs who were significantly younger and had significantly less cognitive impairment than PLWDs in the other patterns. In the Incongruent, PLWD Moderate Involvement pattern, PLWDs had significantly better QOL than PLWDs in the Incongruent, PLWD Low Involvement pattern, but QOL did not significantly differ from PLWDs in the Congruent, PLWD High Involvement pattern. Discussion and Implications: There is a need to tailor strategies to optimize QOL in African American dementia dyads. While increasing everyday decision-making involvement for PLWDs in the Incongruent, PLWD Low Involvement pattern is an important goal, other strategies may be needed to improve the QOL of PLWDs in the remaining patterns.